Properties of Concrete Containing Recycled Coarse Aggregates and Fly ash - Ahmed, Shaikh (RILEM Publications, 2011)
This paper reports the properties of concrete containing recycled coarse aggregate (RCA) and fly ash (FA) obtained from local source in Perth, Western Australia (WA). RCA is used as 25, 50, 75 and 100% (by wt.) replacement of natural coarse aggregate (NCA). In addition, the effect of 40% (by wt.) class F fly ash as partial replacement of cement on the properties of recycled aggregate is also evaluated. The properties of concrete evaluated are the compressive strength, indirect tensile strength, flexural strength and water absorption. All properties are measured at 7, 28, 56 and 91 days. The results show that, better compressive, tensile and flexural strength of concrete containing 25% RCA as partial replacement of NCA can be obtained in recycled aggregate concrete. However, in the case of recycled aggregate concretes containing 40% FA the compressive strength at later ages such as at 56 and 91 days is increased but the indirect tensile and flexural strengths are decreased at all ages. It is observed that the water absorption is decreased as RCA content increased. It is also observed that the water absorption is decreased significantly in recycled aggregate concretes containing 40% FA at all ages.